AJEG BALI: POLITIK IDENTITAS DAN IMPLEMENTASINYA PADA BERBAGAI AGEN SOSIALISASI DI DESA PAKRAMAN UBUD, GIANYAR, BALI - Maryati, Tuty (2012)
Bali is known as a very popular tourist destination area, not only in Indonesia but also overseas. The tourism is supported by the cultural identity of Balinese ethnic, its customs and culture which are based on the values of Hinduism and Tri Hita Karana philosophy. The sociocultural change which is an impact of modernization, globalization, tourism growth and the inflow of other ethnics threatens the identity of Balinese ethnic. It has developed a politics of identity known as Ajeg Bali.Desa Pakraman is a traditional institution that becomes the basis of implementation and the agent of socialization of Ajeg Bali movement. It has many social and religious institutions that are considered as a cultural twist of Balinese culture. Desa Pakraman Ubud is well known as 'kampung global' (global village). In relation to the cultural and tourism identity preserve, Desa Pakraman Ubud applies the politics of identity of Ajeg Bali movement. Related to these reasons, this research focuses on some problems: (1) Why does the community of Desa Pakraman Ubud carry out the retention of ethnic identity through the politics of identity of Ajeg Bali movement?; (2) What is the pattern of the retention of ethnic identity through Ajeg Bali in Desa Pakraman Ubud?; (3) What is the implication of the retention of ethnic identity through Ajeg Bali toward inter-ethnic relations in Desa Pakraman Ubud?This study employs qualitative research with an ethnography approach. The site of this research is Desa Pakraman Ubud, Gianyar, Bali. The data were collected from interview, direct observation to the site, and document analysis. The data were analyzed by considering emic and etic perspektives. The results of the study demonstrates that the practice of the politics of identity of Ajeg Bali movement in Desa Pakraman Ubud emerges as a retention of cultural identity of Balinese ethnic towards the politics of culture from Orde Baru, modernization, globalization, and a retention toward the non-Balinese ethnic. The politics of identity of Ajeg Bali movement takes place in kuren and dadia, desa pakraman, desa dinas, subak, sekaa, puri and geriya for informal education. On the contrary, it takes place in schools for formal education. For non formal education, it occurs in mass media. The application of this movement has an implication to an affirmation of desa pakraman's position and the inter-ethnic relations which bring an ethnocentrism concept, stereotype and ethnic prejudice. It also causes an implication on associative, dissociative and adaptive social process.Key words: Ajeg Bali, politics of identity, retention of ethnic identity, agents of socialization